1996
DOI: 10.1080/07373939608917197
|View full text |Cite
|
Sign up to set email alerts
|

Short-Time Drying of Beatsensitwe, Biologically Active Pulps and Pastes

Abstract: Tomato concentrate and baker's yeast suspension were dried in the laboratory scale Mechanically Spouted Bed dryer with inert packing. Due to a large contact d a c e provided by the inert particles, very fast drying process can be achieved, ifthe thickness of the wet coating formed on the surface of the inert packing is film-like. The d&ion resistance can be then considered negligible and dq4mg can be performed at "quad-constant" rate. Derived fiom hydrodynamic characteristics the contact time between hot air a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
0
7
0
7
Order By: Relevance
“…It has been reported that each plateau on the drying curves corresponds to one such case-hardened state. [42] According to Jumah et al, [43] several kinds of fruits have similar characteristics that make the drying treatment more complicated. Materials exhibiting such behavior are characterized by low melting sugars and present serious drying problems arising from the properties of the solid phase.…”
Section: Results and Discussion Drying And Shrinkage Curvesmentioning
confidence: 99%
“…It has been reported that each plateau on the drying curves corresponds to one such case-hardened state. [42] According to Jumah et al, [43] several kinds of fruits have similar characteristics that make the drying treatment more complicated. Materials exhibiting such behavior are characterized by low melting sugars and present serious drying problems arising from the properties of the solid phase.…”
Section: Results and Discussion Drying And Shrinkage Curvesmentioning
confidence: 99%
“…To provide a smooth drying operation any case hardening, drying rate must be low. For this, it is possible to operate either at low temperature or increase the humidity of the medium, or both as to keep the surface of the drying material plasticized (Karatas & Esin, 1994;Szentmarjay, Pallai, & Regenyi, 1996). Prolonged drying could, however, cause severe degradation in the sensory and the nutritional properties of the tomato.…”
Section: Introductionmentioning
confidence: 97%
“…Since then, this technique has been used for drying chemicals (Mathur and Epstein, 1974;Ormos and Blickle, 1980) as well as biological products such as: animal blood, animal blood plasma, egg white, and protein-containing solutions, among others (Fane et al, 1980;Pham and Pooley, 1981;Pham, 1983;Rashkovskaya et al, 1979;Kutsakova and Utkin, 1983). More recently, reports by Markowski (1992), Reyes et al (1998), Brereton and Lim (1993), Ochoa-Martínez et al (1993), Szentmarjay et al (1996) and Tia et al (1995) who dried a variety of products, ranging from chemicals to liquid foods, have shown the feasibility of the process to obtain good quality dry powdered solids, which make the system, a low-cost, compact alternative to spray drying. Most of these authors have worked with conventional spouted beds, and practically none of them mention any limitations to the system employed.…”
mentioning
confidence: 97%